Exploring the Future Social Identity of a PhD Student Dealing With Anxiety: A Psychotherapy Client Study - Nicholas Sarantakis (Psychotherapy and Counselling Journal of Australia)
This psychotherapy case study examines the brief therapeutic journey of a young woman presenting with academic anxiety and the flexible person-centred approach adopted by her therapist, the author. Application during therapy sessions of concepts from humanistic therapy and beyond, such as configurations of self and imagining future possible selves, enabled the client to unravel her anxiety and eventually discover the underlying tension existing between her internal versus external locus of self-evaluation and self-worth, leading her to contemplate her overall social identity and future life choices. The study aimed to stimulate in the client open reflection about how an internal dialogue between parts of the self may reveal underlying internal tensions and how envisaging possible future selves can help identify how self-criticism may be socially and culturally conditioned. This study, being a single-client study, was tailored for the specific therapeutic goals and personality of the client, and thus the generalisability of this therapeutic approach is limited. However, the study aims to shed light on how we may better support through psychotherapy and counselling students at elite universities with a working-class background, who commonly struggle to "fit in" to this environment and make sense of their changing present and future social identity.